PENINGKATAN KEMAMPUAN BERPIKIR SIMBOLIK MELALUI MEDIA KODE SIMBOLIK WARNA PADA ANAK USIA 5-6 TAHUN DI RA DZIKRURRAHMAN - Arsela, Anis; Dewi Siti Aisyah; Nancy Riana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the increase in symbolic thinking skills through the color symbolic code media in children aged 5-6 years in group B2 at RA Dzikrurrahman Karawang. The problem identified in the pre-cycle stage was the low ability of children to recognize number symbols, letter symbols, and represent symbols through words or images, with a class average percentage of only 42.08%. This study used a Classroom Action Research (CAR) method based on the Kemmis and McTaggart spiral model, which was conducted in two cycles. Each cycle consisted of four main stages: planning, acting, observing, and reflecting. The subjects of this study were 11 children aged 5-6 years old, consisting of 5 boys and 6 girls. Data collection techniques were carried out through triangulation, including observation, documentation, and interviews. Data analysis techniques used descriptive statistical analysis for quantitative data and qualitative analysis consisting of data reduction, data display, and conclusion drawing. The results showed a significant increase in children's symbolic thinking skills. The class average percentage in the pre-cycle was 42.08%, which then slightly increased to 45.83% in Cycle I. After improvements were made to the learning strategy and media variation, the average percentage increased significantly to 86.16% in Cycle II, exceeding the research success criterion of 71%. Based on these results, it can be concluded that the implementation of the color symbolic code media can effectively improve the symbolic thinking skills of children aged 5-6 years at RA Dzikrurrahman.